Konflik Bersenjata Modern dan Domain Hukum - Farras Zakia Rahman; Rangga Andi Yoga; Dwi Imroatus Sholikah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Contemporary defense and security challenges now come from both non-military threats (such as cyber attacks, disinformation campaigns, and economic pressure) and military threats (traditional armed force). These often operate in the gray zone, meaning actions are taken below the threshold of armed conflict as defined under international law. This situation signals the rise of modern armed conflict, which is growing more intense and causing a crisis in International Humanitarian Law (IHL) enforcement. This study aims to describe modern armed conflict and its challenges to IHL. The research used a normative juridical approach and analyzed statutes. Legal materials reviewed included various international legal instruments, which were examined qualitatively and normatively. The results show that modern armed conflict challenges International Humanitarian Law with non-linear conflicts (conflicts with unclear frontlines or participants), proxy actors (groups acting on behalf of states), and cyber threats or propaganda. Therefore, IHL should be updated to include more comprehensive regulations